Effective Access to Multivalent Inhibitors of Carbonic Anhydrases Promoted by Peptide Bioconjugation. Issue 28 (27th March 2017) - Kanfar, Nasreddine; Tanc, Muhammet; Dumy, Pascal; Supuran, Claudiu T.; Ulrich, Sébastien; Winum, Jean‐Yves
Abstract: Multivalency has impressive effects on (bio)molecular recognition, through the simultaneous presentation of multiple copies of a ligand, which can change a weak millimolar binder into a potent nanomolar one. The implementation of multivalency in enzyme inhibition is rather recent, being exemplified by few serendipitous discoveries, and hitherto relying on the random exploration of new multivalent structures as potential enzyme inhibitors. Here, a straightforward and versatile method is reported that enables the construction of multivalent systems for the inhibition of carbonic anhydrases (CA), widespread enzymes that catalyze a fundamental biochemical reaction. Oxime and hydrazone click‐type bioconjugation techniques were successfully used for the preparation of tetravalent peptide conjugates tethered with sulfonamide CA inhibitors. The enzyme inhibition assays show that multivalent effects were present with these novel compounds, but also reveal various structural effects provided by the scaffolds. The versatility of this approach may facilitate the exploration of structure–activity relationships for other types of enzyme inhibitors. Abstract : The application of multivalency in enzyme inhibition has been recently exemplified by a few serendipitous discoveries. Here, a straightforward and versatile method that enables the effective construction of multivalent peptide‐based systems for the inhibition of carbonic anhydrases is reported. The enzyme inhibition assays show that multivalent effects were present with these novel compounds.